Soviet-Iraqi relations during the Iraq-Iran war (1980-1988) is a political historical study - محەممەد, كەمال عەلی; محەممەد, هەستیار محەممەد عەلی سەید (Sulaimani Journal for Humanities, 2025)
Our research deals with an important era in Iraqi-Soviet relations, the period of the Iran-Iraq War, also known as the First Gulf War of 1980-1988. When the Soviet Union was one of the two great nations in the world. When the war began, the Soviet Union did not support Iraq in the war with Iran. It did the opposite in the first two years of the war and supported Iran with weapons and war equipment. Iran is a Soviet weapon that Iraq has taken from that country before or during the war. If the events change, the Soviets, the pro-Iraq state and its supporters since the mid-1980s, have been divided in the past century. The first topic : The Iraqi-Soviet Relations (1980-1984) The Iraqi-Soviet relations highlighted the first four years of the war and the nature of relations between the two countries.. The second topic : In this study we discussed the development of the Soviet-Iraqi relations in the years 1985-1988, the secret of 1984-1986 , when the Americans were secretly supporting Iran, and when the deal was exposed, the Soviet position changed dramatically and became the main and main supporter of Iraq in its war with Iran..